ENHANCING STUDENT ENGAGEMENT AND MOTIVATION THROUGH EDUCATIONAL GAMES: A SYSTEMATIC LITERATURE REVIEW ON TECHNOLOGY INTEGRATION IN SCHOOLS - Seituni, Siti; Muhtar, Wahidi; Anam, Moch Choirul; As'ari, Akhmad Asad; Aditiya, Moh (Journal on Research and Review of Educational Innovation, 2024)
Information and communication technology is currently experiencing very rapid development, especially in the world of education, which is increasingly developing, especially in learning media, where many schools have not utilized technology in learning, so students feel bored in class. This type of literature review research uses the systematic literature review method. Based on the results of a systematic literature review, several researchers used Publish or Perish with the help of other applications such as Zotero Mendeley, VOSViewer, and Microsoft Excel. The selected articles all have good values for the influence of educational games on student learning motivation. The analysis results show that educational games provide an engaging and interactive way to learn, thus encouraging students to be more active and involved in the educational process. These studies support integrating technology in education as an effective strategy to improve school learning quality.